Satisfactory levels on planned fitness programme among adults clarity employees. / Chee Hian Tan … [et al.] - Tan, Chee Hian; Hasan, Hosni; Raja Azidin, Raja Mohammed Firhad; Ismail, Hashbullah; Sharir, Raihana; Salleh, Razali; Mohd Noor, Mohad Anizu (Universiti Teknologi MARA, 2021)
The Satisfactory levels perceived and experiences from one planned fitness programme Fat to Fit- Just Do. It was for a group of clarity employees and adopted instrument’s reliability was r = .965. Its’ consisted of 8 dimensions: General Satisfaction, Treatment to Participants, Personal Skills of Participants, Instructors’ Presentation Skills, Instructors’ Effectiveness, Skill Acquisition, and Teamwork among Instructors with several items in each dimension. Participants were volunteer basis and had undergone one planned theory and practices session within one and the half day programme. The programme was fruitful which covered of fitness test, evaluation, dietarily and nutrition measurement among participants. Resulted descriptively showed highly satisfactory level achieved among 33 (Males = 8., Females = 25). Perhaps, experiential education theory based on outcome of this study showed all dimensions were undoubtfully at satisfied or very satisfied level (45% and 52% respectively). In addition, the study had justified those dimensions were gone through non parametric systematic with Kruskal Willis statistical method analysed by Friedman test ranked the most satisfied and to the least satisfied with mean rank from Instructor Presentation (4.75,1)., Instructor’ Effectiveness (4.55,2)., Personal Skill (4.50,3)., Teamwork of Instructor (4.45, 4)., Treatment to Participants (4.32, 5)., Skill Acquisition (4.24, 6)., General Satisfaction (4.23,7) respectively. This result concluded that fulfilled of the outcome - based education concerned. Therefore, it is highly recommended for implementation of more fitness programme such as Fat to Fit and at the same time considered researchers’ team of this programme were brilliant instructors in performing their expertise to conduct fitness programme and awareness of adults on important of self- fitness concerned.